The Inhibition of the Components from Shengmai Injection towards UDP-Glucuronosyltransferase - Jiang, Li-Peng (Evid Based Complement Alternat Med, 2014)
The mechanism of shengmai injection- (SMI-) related drug-drug interaction remains unclear. Evaluation of the inhibition potential of SMI's ingredients towards UDP-glucuronosyltransferases (UGTs) activity will provide a new insight to understand SMI-related drug-drug interaction. In vitro incubation system to model UGT reaction was used. Recombinant UGT isoforms-catalyzed 4-methylumbelliferone (4-MU) glucuronidation and UGT1A4-catalyzed trifluoperazine (TFP) glucuronidation reactions were employed to phenotype the inhibition profile of maidong's components towards the activity of UGT isoforms. Different inhibition potential of maidong's components towards various UGT isoforms was observed. Based on the inhibition kinetic investigation results, ophiopogonin D (OD) noncompetitively inhibited UGT1A6 and competitively inhibited UGT1A8, ophiopogonin D′ (OD′) noncompetitively inhibited UGT1A6 and UGT1A10, and ruscorectal (RU) exhibited competitive inhibition towards UGT1A4. The inhibition kinetic parameters were calculated to be 20.6, 40.1, 5.3, 9.0, and 0.02 μM, respectively. In combination with our previous results obtained for the inhibition of UGT isoforms by ginsenosides and wuweizi components, the important SMI ingredients exhibiting strong inhibition towards UGT isoforms were highlighted. All the results obtained in the present study provide a new insight to understand SMI-related drug-drug interaction.